RATE COEFFICIENT CALCULATIONS ON THE 3-DIMENSIONAL D+HC1-]DC1+H REACTION USING A NEW QUANTUM-DYNAMICAL APPROXIMATION - Clary, D (1981)
Rate coefficient calculations for the three-dimensional D + HCl→DC1 + H reaction are reported. A new quantum method is used, which involves applying the energy sudden approximation to the entrance channel and the centrifugal sudden approximation to the exit channel. Good agreement with quasiclassical results is obtained. © 1981.